Comparative study of autonomic dysfunction between Parkinson’s disease with LRRK2, PRKN, and GBA mutations - Bárbara Maldotti Dalla Corte; Bárbara Maldotti Dalla Corte; Nayron Medeiros Soares; Eurípedes Gomes de Carvalho Neto; Eurípedes Gomes de Carvalho Neto; Carlos Roberto de Mello Rieder; Carlos Roberto de Mello Rieder (Frontiers in Neurology)
BackgroundAutonomic symptoms are among the most important factors determining the quality of life in patients with Parkinson’s disease (PD). This study aimed to assess the profile of autonomic dysfunction symptoms in three groups of patients with genetic PD, carrying mutations in GBA, LRRK2, and PRKN genes, compared with subjects with sporadic PD.MethodsThis case–control observational secondary analysis of prospectively collected data was performed on 742 patients (485 in the sporadic group, 165 in the LRRK2 group, 85 in the GBA group, and nine in the PRKN group). Autonomic symptoms were evaluated using the Scale for Outcomes in Parkinson’s Disease-Autonomic (SCOPA-AUT).ResultsThe GBA group exhibited more severe autonomic linsymptoms than the sporadic group, even after controlling for potential confounders such as disease duration and levodopa equivalent daily dose (linear regression B value = −4.668; Total SCOPA-AUT: p = 0.050; LEDD: p = 0.966; Disease Duration: p = 0.498). The LRRK2 group initially showed more autonomic symptoms, but this did not remain significant after adjustment for disease duration (B value = −3.105; p = 0.189). The PRKN group did not differ significantly from the sporadic group. Subgroup analysis highlighted specific issues including constipation, early satiety, and heat intolerance in both the GBA and LRRK2 groups, orthostatic hypotension in the GBA group and urinary incontinence and excessive perspiration in the LRRK2 group. Despite these subjective reports, objective assessment for orthostatic hypotension revealed no significant inter-group differences.ConclusionThese findings that genetic background may influence the severity of autonomic dysfunction in PD. In particular, patients with GBA mutations appear to experience a greater autonomic symptom burden, underscoring the need for personalized clinical monitoring and further research into genotype-specific disease progression. However, inconsistencies between subjective reports and objective autonomic measures emphasize the importance of employing more refined and sensitive assessment tools. Larger and demographically balanced cohorts are required to confirm these results, especially for the underpowered PRKN.